A conceptual framework on organisational citizenship behaviour in educational institutions based on servant leadership philosophy - Adnan, Ezwati; Othman, Azam; Amzat, Ismail Hussein; Miraz, Mahadi Hasan (2025)
Employee organisational behaviour is crucial in educational institutions as it enhances performance, drives development, fosters transformation and innovation and improves efficiency. In Malaysia, teachers’ well-being and school atmosphere are affected by heavy workloads and burnout. The reliance of Muslim teachers on their spiritual beliefs and Islamic principles is paramount in shaping their professional identity and well-being within educational settings. While Servant Leadership improves school climates globally, its impact in Malaysia’s socioreligious context remains understudied. This study proposes an enriched theoretical framework and practical insight into how Servant Leadership enhances Organisational Citizenship Behaviour and teacher well-being through Sejahtera Living.